Pengaruh Media Sosial, Kualitas Produk, Dan Kepuasan Pelanggan Terhadap Keputusan Pembelian (Studi Pada Lelette Coffee Sigura-Gura) - Muhammad Maulana Habibi; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and determine the effect of Social Media, Product Quality, and Customer Satisfaction on Purchasing Decisions (Study on Lelette Coffee Sigura-gura Malang). This research is a type of quantitative research. The method used is multiple linear regression. The sampling technique uses the formula from Malhotra with a calculation of 95 samples. To overcome the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results of the study show that Social Media (X1), Product Quality (X2), and Customer Satisfaction (X3) simultaneously have a significant effect on purchasing decisions (Y). The results of the study partially show that Social Media (X1), Product Quality (X2), and Customer Satisfaction (X3) partially have a significant effect on Purchasing Decisions (Y). Keywords: Social Media, Product Quality, Customer Satisfaction, Purchase Decision